The Ethnobotany of traditional medicinal plants used in Senapati district of Manipur, Northeastern India - Thokchom Biona
This study presents data on important ethnomedicinal plants that were gathered from Manipur's Senapati District. Modern medical facilities are lacking in this area, and traditional health care systems are still practiced. A total of 82 plant species under 46 families were documented from 23 informants. Questionnaires that were open-ended and semi-structured were used to collect the data. Ethnobotanical indices were used to indicate ethnomedicine's advantages, significance, and application. The highest ICF value was 1 for kidney diseases, general health or body weakness, and oral care, followed by skin diseases (0.76). Rhus chinensis Mill (0.52) has the highest relative frequency of citation value followed by Zingiber officinale Roscoe (0.39), Psidium guajava L. (0.39), Gynura cusimbua (D.Don) S.Moore (0.35), Oroxylum indicum (L.) Kurz (0.35). Decoction (47%) was the most commonly used method of preparation followed by raw/fresh (22%), paste (8%), juice (8%), crushed (10%), powder (2%), infusion (2%) and maceration (1%). In our study, 11 plant species were found to have a 100% fidelity level. These species could be a real natural reservoir of new biomolecule with a potential pharmacological activity. Therefore, the preservation of this heritage by documentation and scientific studies is an essential requirement.